Numerical Simulation of Quantum Efficiency of Cd0.8Zn0.2S /CIGS Solar Cells - Ihalane, E.; Atourki, L.; Alahyane, L.; Kirou, H.; Boulkaddat, L.; hamri, E. El; Ihlal, A.; Bouabid, K. (Journal of Technology Innovations in Renewable Energy, 2014)
The paper presents a simulation study using the numerical simulator SCAPS-1D to model ZnO/Cd0.8Zn0.2S/CuIn(1-y)GaySe2/CuInSe2 structures. Effects of thickness of graded and ungraded CIGS absorbers and buffer layers on cell performance have been investigated with the aim to reach a higher efficiency. Quantum efficiency (QE) as function of wavelength and thickness of these layers was studied. The high efficiency of CIGS cells, in order of 22.05%, has reached with the absorbers thickness between 2μm and 3.5μm and with acceptor concentration of about 2.1016 cm3. Other hand, we investigate the effect of Cd0.8Zn0.2S ternary compound buffer on the top of the p-CIGS cell. These simulation results give some important indication to enable further development of multilayer thin-film solar cells based on CuInGaSe2 with Cd0.8Zn0.2S as buffer layer instead of CdS